2000
DOI: 10.1029/2000jc900084
|View full text |Cite
|
Sign up to set email alerts
|

Undertow over a barred beach

Abstract: Abstract. The spatial distribution of the mean cross-shore flow (undertow) over a barred beach is examined with field data obtained on three energetic wave days during the Duck94 experiment. The vertical structure of the undertow is modeled using a turbulent eddy viscosity closure and includes the important effects of wave breaking (described using the roller concept) and convective acceleration of the current. Other than a more realistic description of observed turbulence variations, a depth-dependent eddy vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(33 citation statements)
references
References 29 publications
3
29
0
1
Order By: Relevance
“…From the new non‐dimensional ϵ scaling , the non‐dimensional eddy diffusivity K is K(z)h()dF/dx1/3=δ4/3A1/3expα3zh, a different vertical structure than the commonly assumed constant [ Faria et al , 2000] or log‐profile [ Beach and Sternberg , 1988; Denny and Shibata , 1989] based ≈ u * κz (where u * is the bed friction velocity). The dimensional K depends on wave breaking (d F /d x ) analogous to earlier dimensional analysis [ Battjes , 1975].…”
Section: Discussionmentioning
confidence: 99%
“…From the new non‐dimensional ϵ scaling , the non‐dimensional eddy diffusivity K is K(z)h()dF/dx1/3=δ4/3A1/3expα3zh, a different vertical structure than the commonly assumed constant [ Faria et al , 2000] or log‐profile [ Beach and Sternberg , 1988; Denny and Shibata , 1989] based ≈ u * κz (where u * is the bed friction velocity). The dimensional K depends on wave breaking (d F /d x ) analogous to earlier dimensional analysis [ Battjes , 1975].…”
Section: Discussionmentioning
confidence: 99%
“…At each frame, the friction velocity u * is estimated from the alongshore bottom stress (6) as u 2 * 5 c d hjujyi, where the best-fit c d 5 2.3 3 10 23 (section 4a). Although the crossshore bottom stress can also contribute to the total bottom stress and thus u * , because of the strong vertical structure of the mean cross-shore current (Faria et al 2000), it is unclear whether a quadratic drag law is applicable for the cross-shore bottom stress t b…”
Section: Bbl Scalingmentioning
confidence: 99%
“…In a surf zone characterized by an alongshore homogeneous morphology, the onshore Stokes drift profile is vertically uniform, and the Eulerian undertow flow has a parabolic velocity profile with maximum offshore velocity at middepth or near bottom (Svendsen 1984;Putrevu and Svendsen 1993;Haines and Sallenger 1994;Garcez Faria et al 2000;Reniers et al 2004b), resulting in an imbalance between u St (z) and u E (z) throughout the water column (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…A compensating wave-driven offshore Eulerian flow u E (z) exists below the wave trough, referred to as undertow. The presence of wave-driven Eulerian undertow inside the surf zone is widely known and has been measured extensively in the field (Haines and Sallenger 1994;Garcez Faria et al 2000;Reniers et al 2004b) and has also been found to extend well offshore on the inner shelf (Lentz et al 2008;Kirincich et al 2009;Ohlmann et al 2012). The summation of u St (z) and u E (z), throughout the water column at a given location, results in a wave-averaged Lagrangian velocity u L (z), where z is the vertical elevation defined as positive upward from the sea surface.…”
Section: Introductionmentioning
confidence: 99%